2022
DOI: 10.1177/00031348221074245
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insurance Status on Bariatric Surgery Outcomes: A Retrospective Chart Review Study

Abstract: Background Prior studies have shown socioeconomic factors and race to affect weight loss after bariatric surgery, but few have focused on the impact of insurance status. The purpose of this study was to determine if insurance status affects bariatric surgery patients’ surgical outcomes and weight loss. Methods A retrospective review was conducted of 408 bariatric patients who underwent laparoscopic Roux-en-Y gastric bypass (LRYGB) or sleeve gastrectomy (SG). Patients were stratified by insurance status and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…However, LT patients were more likely to have public insurance and undergo RYGB. Univariate analysis showed greater 1-year weight loss among LT patients; however, this was not statistically significant on multivariate analysis, consistent with other studies which showed SES did not affect short-term weight outcomes [ 7 , 11 , 17 ]. This finding is encouraging as it indicates that, despite poorer resources, LT patients can have the same short-term weight loss benefits as their HT counterparts.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, LT patients were more likely to have public insurance and undergo RYGB. Univariate analysis showed greater 1-year weight loss among LT patients; however, this was not statistically significant on multivariate analysis, consistent with other studies which showed SES did not affect short-term weight outcomes [ 7 , 11 , 17 ]. This finding is encouraging as it indicates that, despite poorer resources, LT patients can have the same short-term weight loss benefits as their HT counterparts.…”
Section: Discussionsupporting
confidence: 86%
“…It is crucial to understand the risk factors that affect weight outcomes, especially since the magnitude and maintenance of weight loss significantly impacts improvement in metabolic health and obesity-associated comorbidities. SES has been implicated as one such risk factor, but measures of SES and its effect on weight loss have been variable [ 5 , 7 , 9 , 10 ]. Given its role as a comprehensive measure for SES, we used DCI as a means to better understand the impact of SES on weight loss and weight recurrence after bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In female patients, age is negatively associated with weight-loss outcomes, as has been demonstrated in a large number of studies ( 26 29 ). The basal energy expenditure has a tendency to decrease tremendously with age, switching from 60 to 70% of total metabolism around the age of 20–30 to 40% at the age of 50 ( 30 ).…”
Section: Discussionmentioning
confidence: 70%